2002
DOI: 10.5194/angeo-20-539-2002
|View full text |Cite
|
Sign up to set email alerts
|

Are variations in PMSE intensity affected by energetic particle precipitation?

Abstract: Abstract.The correlation between variations in Polar Mesosphere Summer Echoes (PMSE) and variations in energetic particle precipitation is examined. PMSE were observed by the Esrange VHF MST Radar (ESRAD) at 67 • 53 N, 21 • 06 E. The 30 MHz riometer in Abisko (68 • 24 N, 18 • 54 E) registered radio wave absorption caused by ionization changes in response to energetic particle precipitation. The relationship between the linear PMSE intensity and the square of absorption has been estimated using the Pearson line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
1
18
2
Order By: Relevance
“…This result agrees with Barabash et al (2002) whereby there is no significant correlation between PMSE variations and cosmic noise absorption. However, Morris et al (2005) found a very weak correlation of PMSE, observed by VHF radar, and cosmic noise absorption.…”
Section: Superdarn-pmse Occurrence In Relation Tosupporting
confidence: 82%
“…This result agrees with Barabash et al (2002) whereby there is no significant correlation between PMSE variations and cosmic noise absorption. However, Morris et al (2005) found a very weak correlation of PMSE, observed by VHF radar, and cosmic noise absorption.…”
Section: Superdarn-pmse Occurrence In Relation Tosupporting
confidence: 82%
“…Bremer et al, 1995;Rapp et al, 2002;Barabash et al, 2004). Analyses Bremer et al (2000Bremer et al ( , 2001 and Barabash et al (2002) concentrating mainly on the diurnal variation of the correlation between PMSE and geomagnetic activities. Other investigations estimate the correlation between monthly mean values of (P)MSE and geomagnetic indices .…”
Section: Introductionmentioning
confidence: 99%
“…Absorption intensity has also been shown to correlate well with the X-ray counting rate at ∼30 km (Brown and Barcus, 1963) and the magnetic disturbance level associated with the electrojet currents at 100-110 km measured by magnetometers (Brown and Campbell, 1962;Hargreaves, 1966;Kavanagh et al, 2004). Positive correlation has been reported between the CNA and Polar Mesospheric Summer Echo (PMSE) intensity (Czechowsky et al, 1989;Kirkwood et al, 1995;Klostermeyer, 1999;Barabash et al, 2002) as observed by VHF radars, although statistically the correlation appears to be rather weak (Czechowsky et al, 1989;Bremer et al, 2000;Barabash et al, 2002). In this paper we attempt to advance our knowledge of the processes leading to the enhanced cosmic noise absorption by exploring the relationship between the riometer absorption and backscatter power of auroral echoes detected by a VHF coherent radar.…”
Section: Introductionmentioning
confidence: 69%
“…Czechowsky et al, 1989;Kirkwood et al, 1995;Barabash et al, 2002). One should bear in mind, however, that the vast majority of the PMSE observations have been performed with vertical incidence VHF radars at frequencies near 50 MHz, while our measurements were carried out with an oblique-sounding 144-MHz radar, sensitive to fieldaligned irregularities in the E region.…”
Section: Discussionmentioning
confidence: 99%